To solve for x in the equation 1.5 - x = -4.5, we need to isolate x on one side of the equation.
First, let's subtract 1.5 from both sides of the equation:
1.5 - x - 1.5 = -4.5 - 1.5
This simplifies to:
-x = -6
Next, let's multiply both sides of the equation by -1 to isolate x:
(-1)(-x) = (-1)(-6)
This simplifies to:
x = 6
Therefore, the solution to the equation 1.5 - x = -4.5 is x = 6.
1.5−x=−4.5
3 answers
6y - 9y + 6 = -12
To solve this equation, we will combine like terms and isolate the variable.
Starting with the given equation: 6y - 9y + 6 = -12
We can combine the y terms by subtracting 9y from 6y: -3y + 6 = -12
Next, we will isolate the variable y by subtracting 6 from both sides: -3y + 6 - 6 = -12 - 6
This simplifies to: -3y = -18
To solve for y, we need to divide both sides of the equation by -3: (-3y) / -3 = (-18) / -3
This further simplifies to: y = 6
Therefore, the solution to the equation 6y - 9y + 6 = -12 is y = 6.
Starting with the given equation: 6y - 9y + 6 = -12
We can combine the y terms by subtracting 9y from 6y: -3y + 6 = -12
Next, we will isolate the variable y by subtracting 6 from both sides: -3y + 6 - 6 = -12 - 6
This simplifies to: -3y = -18
To solve for y, we need to divide both sides of the equation by -3: (-3y) / -3 = (-18) / -3
This further simplifies to: y = 6
Therefore, the solution to the equation 6y - 9y + 6 = -12 is y = 6.